2020
DOI: 10.22271/chemi.2020.v8.i4i.9753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weed management strategies on weed count and yield attributes of apple (Malus × Domestica) under high density orchard system

Abstract: A field experiment was conducted during 2018 to assess the effect of different weed management strategies on weed count and yield attributes of apple under high density orchard system. The said investigation was carried out in experimental fields of Division of Fruit Science, SKUAST, Kashmir. One year old trees of exotic apple cv. "Elstar" grafted on M-9 T337 rootstock, introduced from Holland in March 2017, were selected for experimentation. Thirteen selected treatments were laid in randomized complete block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The yield may be explained by the two growth regulators' beneficial effects on the translocation and biosynthesis of carbohydrates, which were reflected in rising fruit numbers and average fruit weight. Results are consistent However, their findings demonstrated that the use of GA 3 and NAA increased yield/tree, fruit weight [34][35][36][37][38]. The higher fruit set from improved flowering and higher hermaphrodite flowers, as well as the altered source-sink relationship in the plant, which directly reallocates the carbohydrate reserves by suppressing the vegetative growth, were the causes of the yield increase in paclobutrazol-treated trees before the bud break, during vegetative growth, paclobutrazol application will not only prevent the increased growth but also increase the yield.…”
Section: Effect Of Pgr's On Yieldmentioning
confidence: 64%
See 1 more Smart Citation
“…The yield may be explained by the two growth regulators' beneficial effects on the translocation and biosynthesis of carbohydrates, which were reflected in rising fruit numbers and average fruit weight. Results are consistent However, their findings demonstrated that the use of GA 3 and NAA increased yield/tree, fruit weight [34][35][36][37][38]. The higher fruit set from improved flowering and higher hermaphrodite flowers, as well as the altered source-sink relationship in the plant, which directly reallocates the carbohydrate reserves by suppressing the vegetative growth, were the causes of the yield increase in paclobutrazol-treated trees before the bud break, during vegetative growth, paclobutrazol application will not only prevent the increased growth but also increase the yield.…”
Section: Effect Of Pgr's On Yieldmentioning
confidence: 64%
“…The impact of the growth regulator treatments on the apple's shelf life under 30 days of ambient storage was significant. [35] No Name of crop Treatment Results References 7.53% was found to be the maximum physiological weight loss (CPLW). Growth regulators reduced the amount of malic acid relative to untreated fruits while increasing TSS, or total sugars, in the fruit.…”
Section: Name Of Crop Treatmentmentioning
confidence: 99%